The Micro-Governance of Collaborative Networks: Promoting Entrepreneurial Ecosystems - Andrei Mikhailov; Kadigia Faccin; Douglas Wegner; Elisa Thomas (Journal of Technology Management & Innovation)
The formation of interorganizational networks for the promotion of entrepreneurial ecosystems is a strategy that is increasingly present in the agenda of public and private actors as an alternative for local development. However, effectiveness is something quite difficult to achieve, and much has been studied about the factors that contribute to the realization of a collaborative environment and which, in turn, become essential for the promotion of innovation ecosystems. One of these elements is network governance. This research intends to fill this gap, analyzing the possible combinations of micro-governance roles that create collaborative environments. Nineteen networks in the initial stages of formation were analyzed in one of the most developed capitals in Brazil. The application of the method of comparative qualitative analysis (QCA) allowed the identification of two combinations of micro-governance roles that allow the interorganizational network to create a collaborative environment.  These combinations showed that roles such as organizing resources (OR), arbitrating tensions (AT) and monitoring efforts and results (MER) are necessary, but not sufficient for the promotion of the collaborative environment. It is expected that obtained results will be useful for practitioners and policy makers which aim the development and growth of interorganizational networks.